Capturing the effects of semantic transparency in word recognition: a cross-linguistic study on Cantonese and Persian. Issue 5 (1st June 2021) - Momenian, Mohammad; Cham, Shuk K.; Mohammad Amini, Jafar; Radman, Narges; Weekes, Brendan
ABSTRACT: An important question in psycholinguistics is whether or not the semantic transparency of words plays any role during the processing of compound words. Studies of different languages have produced mixed results suggesting that semantic properties of compounding do not have a universal effect. This paper uses masked priming at three different SOAs to study the possible effects of semantic transparency and grammatical class on processing of Persian and Cantonese compounds. We found priming effects in all types of compounds across both languages regardless of semantic transparency and grammatical class. Our findings revealed processing patterns which were unique to each language. We contend that compounding is a complex process influenced by the interactions among the unique properties of each language such as productivity, headedness, and the writing system.